Modelo para la gestión de programas en el sector de Telecomunicaciones del Instituto Costarricense de Electricidad - Sánchez-Loría, Javier (Instituto Tecnológico de Costa Rica, 2013)
Implementing a model for Program Management in the Telecommunications Sector forced to watch the program management through a broader and a higher level than project management. Program management must be seen as part of the overall business strategy as a structure that provides support to the Sector and will enable the achievement of long-term goals. The programs focus on achieving the benefits, not only in achieving direct products or deliverables as with the projects. While a project may provide a new service, a new network, etc., A program brings results in terms of new capacities, skills and / or new benefits for the sector and hence for their customers. Therefore, project management through programs becomes a differentiating factor for the Telecommunication Sector and for ICE, which can provide advantages in a competitive environment. A program can arise in different ways. In the case of ICE Telecommunications Sector, it is considered that a program can be started from: a business case, the Sector's strategic plan, structures or existing policies, as well as the identification of benefits to be gained through the execution of a program. The program charter is the most important document in the initiation stage of the program. Through the charter, the Strategic Portfolio Office shall approve a program. The profile describes what the program purpose is, the reasons for which you intend to run it, the expected benefits, the scope and how this contributes to the achievement of objectives of the Sector. The document provides basic information from which to take the decision to approve the program, and then provide the basis for the planning stage. The planning phase aims to align the program with the strategic objectives of the sector through the development of the management plan leading to obtain the benefits and objectives, from the point of view of various areas of knowledge. The program management model of the Telecommunications Sector ICE will take processes and tools based on PMI Program Management standard, for the knowledge areas of Scope, Time, Risk, Communications, Involvement, Finance and Acquisitions. The proposed program management focuses on the principle of simplicity in terms of documentation, not to overwhelm the program director with an excess of templates and documents. The main output of the integration knowledge area is the program management plan, which integrates the various plans that are made by area. The management plan forms the basis from which the program is executed. Execute the program is synonymous with implement the plan, hence its importance. The program is managed throughout the life cycle under a governance framework, which aims to ensure program alignment with the strategic plan of the institution, and that it is performed in accordance with the policies and objectives approved by senior management, and that it meets the expectations under which it was established. Governance allows the program manager to assess the evolution of it and take necessary actions, and also allows collaborators to have the necessary guidance and identify the expected outcomes of their work. The structure must support the program providing the environment, tools and mechanisms necessary for the program to run effectively, ensuring that the communications process flow as planned, to take appropriate decisions and that these decisions are properly documented, and the roles and responsibilities are well defined. The programs, like the projects have a beginning and an end. However, the programs cover a period of time much larger than a project and can even evolve as new needs arise. May still be active until it is satisfied that its objectives and expected benefits have already been completed, or, even when you consider that the program no longer provides the strategic framework of the Sector. In any case the closure of a program should be conducted in an orderly fashion, documenting the process and results. The program manager is the person assigned by the Telecommunications Sector for planning and implementing the objectives and benefits of the program. He or she must be a person with leadership, with extensive experience in the industry, as well as technically competent for the position, able to translate the strategic objectives of the Sector in a plan with objectives and clear benefits, and the ability to convey the vision of the program others. The competencies of a program director include their knowledge, skills and attitudes. This three elements define the characteristics to be met by a person who intends to run a program in the Telecommunications Sector.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2011.
Keywords: Administración; Gestión de proyectos; Telecomunicaciones; Programas; Perfiles administrativos